Deterministic integration of single nanowire devices with on-chip photonics and electronics. (August 2022) - Jevtics, D.; Guilhabert, B.; Hurtado, A.; Dawson, M.D.; Strain, M.J.
Abstract: The epitaxial growth of semiconductor materials in nanowire geometries is enabling a new class of compact, micron scale optoelectronic devices. The deterministic selection and integration of single nanowire devices, from large growth populations, is required with high spatial accuracy and yield to enable their integration with on-chip systems. In this review we highlight the main methods by which single nanowires can be transferred from their growth substrate to a target chip. We present a range of chip-scale devices enabled by single NW transfer, including optical sources, receivers and waveguide networks. We discuss the scalability of common integration methods and their compatibility with standard lithographic methods and electronic contacting.